2016
DOI: 10.1177/1753193416638483
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of symptomatic non-unions of the base of the ulnar styloid with plate osteosynthesis

Abstract: Therapeutic IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The latter implies higher-energy trauma with a potential risk of distal radioulnar ligament tear and may serve as a marker for injury severity [ 17 ]. Articles favoring conservative treatment primarily emphasized successful surgical fixation in distal radius fractures, while the injury severity in ulnar styloid fractures per se and the resulting symptoms were generally underestimated and inadequately treated [ 12 ]. It is not our purpose to recommend that all ulnar styloid fractures need to be surgically treated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The latter implies higher-energy trauma with a potential risk of distal radioulnar ligament tear and may serve as a marker for injury severity [ 17 ]. Articles favoring conservative treatment primarily emphasized successful surgical fixation in distal radius fractures, while the injury severity in ulnar styloid fractures per se and the resulting symptoms were generally underestimated and inadequately treated [ 12 ]. It is not our purpose to recommend that all ulnar styloid fractures need to be surgically treated.…”
Section: Discussionmentioning
confidence: 99%
“…Ulnar styloid fractures have been traditionally discussed with distal radius fractures and generally treated conservatively [ 18 ]. Only a handful of articles have reported surgical management and outcomes of ulnar styloid fractures [ 1 , 12 , 19 ]. A current prospective study reported symptomatic nonunion that was successfully treated with plating osteosynthesis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations